The paradox of designing networked learning throughout the employee life cycle - Skårhøj, Simon (Proceedings of the International Conference on Networked Learning, 2024)
How can organisations cultivate professional and social networks which accelerate knowledge sharing throughout the employee life cycle? The increasing complexity of the workplace environment and continuously changing processes makes it relevant for many organisations to invest in their social network structures, communities, and knowledge sharing. However, ultimately these social and relational processes are depended on the employees’ personalities, interests, ownership, and motivation and which do not necessarily correspond with the organisation’s strategy, priorities, timing, and resources. This constitutes a paradox between the strategic priority for networked learning and the employees’ interest and motivation to participate in knowledge sharing. Both elements are true, interconnected and mutually exclusive elements and raise a paradox (Lüscher, 2019:8) for networked learning designers in organisations between intended design and uncertain evolution.